2016
DOI: 10.2474/trol.11.308
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water and Oxygen Molecules in the Lubricity of Carbon Nitride Coatings under a Nitrogen Atmosphere

Abstract: In this study, an experimental apparatus was developed where the relative humidity (RH) and oxygen concentration could be controlled between 0.01-10%RH and 1-100000 ppm, respectively. This apparatus was used to study the roles of water and oxygen molecules on the friction of carbon nitride (CN X) coatings. The friction properties of Si 3 N 4 balls sliding against CN X (Si 3 N 4 /CN X) under a nitrogen atmosphere were classified into the following three modes according to their average friction coefficients (µ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The spectra showed a growth in the D peak and a shift in the G peak toward a higher wave shift compared with that of the initial CN x :H. This change in the Raman spectrum indicates different amorphous structure of the carbonaceous tribolayer from the initial coatings, indicating a transformation into a more graphitic structure. This spectral pro le is similar to that of low-frictional tribolayers with nanometer-scale thickness (less than 10 nm) previously reported in our studies, suggesting a comparable carbon structure [19,[22][23][24]. Similar to those earlier ndings, the carbonaceous tribolayer detected here is also exceedingly thin for optical microscopy detection, supporting its identity as the critical low-frictional tribolayer essential for reducing friction in CN x :H systems, with an inferred thickness of less than 10 nm [19,24].…”
Section: Effect Of Relative Humidity On the Formation Of Lowfrictiona...supporting
confidence: 89%
See 3 more Smart Citations
“…The spectra showed a growth in the D peak and a shift in the G peak toward a higher wave shift compared with that of the initial CN x :H. This change in the Raman spectrum indicates different amorphous structure of the carbonaceous tribolayer from the initial coatings, indicating a transformation into a more graphitic structure. This spectral pro le is similar to that of low-frictional tribolayers with nanometer-scale thickness (less than 10 nm) previously reported in our studies, suggesting a comparable carbon structure [19,[22][23][24]. Similar to those earlier ndings, the carbonaceous tribolayer detected here is also exceedingly thin for optical microscopy detection, supporting its identity as the critical low-frictional tribolayer essential for reducing friction in CN x :H systems, with an inferred thickness of less than 10 nm [19,24].…”
Section: Effect Of Relative Humidity On the Formation Of Lowfrictiona...supporting
confidence: 89%
“…Upon setting the test specimens, the air atmosphere (20-21% O 2 ) inside the case was consistently maintained within the 5-50% RH range using the dehumidi er. For friction tests in air or nitrogen atmospheres with relative humidity ranging from 0.01 to 5% RH, the glovebox-type apparatus was used, as detailed in our previous research [22]. The friction test system was installed within a glovebox (UN-650L, UNICO, Japan), which allowed for control over the relative humidity and oxygen concentration within the chamber using a gas puri er.…”
Section: Ball-on-disk Friction Tests Under Dry Conditions With Contro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Kato and Adachi and Yamada et al revealed that O 2 is a harmless chemical in N 2 for changing friction for self-mated carbon nitride which is one coating type among HF-DLC; however, water vapor affected increasing CoF and wear. Therefore, ta-C/ta-C and Ti-DLC/steel tribopairs could provide low friction in dry environments owing to the establishment of a C / C contact interface.…”
Section: Resultsmentioning
confidence: 99%